Implementasi Kebijakan Kampus Mengajar Sebagai Manifestasi Atas Program Kebijakan Merdeka Belajar - Ismail, My; Syukron, Nurkholis (Jurnal Administrasi Karya Dharma, 2023)
Abstrak This study aims to know about “kampus mengajar” program as manifestation of the “merdeka belajar” policy initiate by Ministry of Education, Culture, Research and Technology of the Republik Indonesia. This study is a qualitative research using the systematic literature review method through collection articles and journals as reference source. The result of this study showed that “kampus mengajar” program in terms of community services as manifestation of the “merdeka belajar” policy is taking place. This program provides students with the opportunity to contribute directly to Indonsesia’s education tangibly. The space is so open given by “kampung mengajar” program for the implementation of devotion to the public, that the cross-disciplined students can have the same opportunity to implement the program. So, the students were content with an intelectual activities can distribute their intelectual experiences to the Indonesia’s students schools.